China’s Influence In Africa: Current Roles And Future Prospects In Resource Extraction - Haifang, Liu (Journal of Sustainable Development Law and Policy, 2025)
In the second half of 2014, some African countries felt the heavy strike of falling prices of mineral resources on the world market. The international media raised vocalex positions on the negative impact that China’s slow down might bring to the African economy. One headline read: “Chinese investment in Africa has fallen 40 per cent this year – but it’s not all bad news”.1 More recently, the exasperation intensified to “China’s slowdown blights African economies”,2 and managed to shadow the China-African Summit held in December 2015 in Johannesburg. Similarly, on the recent Africa Mining Indaba, the annual biggest African event for the mining sector, the renewed concern was stated as “Gloom hangs over African mining as China growth slows”.3 There is no doubt that China’s presence has had positive effects on Africa’s growth over the past decade. Nonetheless, only a narrow perspective would view Africa’s weak performance solely through the Chinese prism. This article addresses the afore-mentioned concerns regarding the impacts that China has in Africa. A historical approach is applied to reconstruct the economic cooperation since the mid-1990s. This reconstruction emphasizes the sustaining forces of cooperation. Literally, this article goes beyond the resource traction sector, to understand the basis of China-African cooperation, and the position mineral resource has taken in the bilateral cooperation. With a representative country case study, the current dilemma is shown from the structure of bilateral cooperation. Suggestions follow on how to address these challenges.